ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KEUANGAN BANK UMUM DI BURSA EFEK INDONESIA - Nazia Fitria Hamdi (2021)
This research includes quantitative research aiming to find out whether there is an influence between liquidity, operational efficiency, bank size, interest rate towards financial performance. The objects in this research are commercial banks listed on Indonesia Stock Exchange (IDX) with 29 commercial banks chosen as the samples within the period of 2018 - 2020. Research hypothesis were tested with the significance level of 5%, using panel data regression model and assisted by E-Views 9 program. The result obtained within this research are (1) liquidity does not significantly influence financial performance (2) there is a significant influence between operational efficiency and financial performance, (3) bank size does not significantly influence financial performance, and (4) interest rate has significantly influence credit lending.